Clinical characteristics and surgical approach for pituitary granular cell tumors: a case series of six patients and literature review - Liu, Jun; Zhang, Wenjun; Huang, Qianliang; Ye, Xinyun; Huang, Guanlin (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinical characteristics and therapeutic approaches for granular cell tumors (GCT) of the neurohypophysis.Materials and methodsRetrospective case series and analyzed the clinical data of six patients with histopathologically confirmed GCT of the neurohypophysis, also conducting a simple review of relevant literature.ResultsThe median age at diagnosis for the cohort of six patients was 41.0 ± 11.73 years, with an age range of 21.8 to 52.7 years. A predominance of female patients was noted, accounting for five out of six cases. The most common clinical symptoms were headache and visual disturbances, each reported in five of the six patients. Magnetic resonance imaging (MRI) of the brain predominantly revealed a rounded morphology, and well-defined boundaries. Of these tumors, two were located in the suprasellar region while four were situated within the sellar region, encompassing intrasellar, suprasellar, and parasellar locations. Contrast-enhanced MRI demonstrated heterogeneous enhancement in four cases and homogeneous enhancement in two cases. Surgical intervention, either through a neuro-endoscopic endonasal transsphenoidal approach or craniotomy, achieved total or subtotal tumor resection in all patients. Postoperative histopathological examination confirmed the diagnosis of GCT in each instance. All patients participated in follow-up evaluations, during which varying degrees of clinical symptom improvement were documented. Importantly, none of the four patients who underwent complete tumor resection exhibited recurrence or metastasis.ConclusionGCT of the neurohypophysis are rarely encountered clinical practice. The definitive diagnosis of GCT primarily relies on histopathological evaluation. Currently, the standard therapeutic approach involves complete surgical excision of the tumor using a neuroendoscopic endonasal transsphenoidal technique. Post-resection, the rates of recurrence and metastasis are significantly low.